Internationalization of Higher Education The Case of Hong Kong - Cheng, Yin Cheong; Cheung, Alan Chi Keung; Ng, Shun Wing (Education in the Asia-Pacific Region: Issues, Concerns and Prospects,, 2016)
This book reviews and analyses the issues and policies of internationalization and exportation of higher education and investigates the strategies and models of education hub development in the context of globalization, with Hong Kong in the Asia-Pacific region as a case study. It examines the close relationship between education hubs and higher education, as well as the strategic functions of an education hub in the future development of a society in a competitive global environment.  It also analyses the major strengths, weaknesses, opportunities, and threats of Hong Kong's higher education in relation to its potential for exporting higher education to Asian markets. In particular, it reviews the current state of higher education services offered by Hong Kong in three target markets and their segmentation and proposes the most appropriate market entry strategies for education service providers.